Safety Advice and Safety Participation in OSHMS among OHSAS 18001 certified Malaysian Manufacturing Companies - Kheng Khor, Lay; Surienty, Lilis (International Journal of Engineering and Technology, 2018)
Lack of safety participation in Occupational Safety, Health and Environment Management System (OSHMS) has exposed employees to high risk of work hazards resulting in high occupational accidents. This does not only affect employeeâ€™s morale towards work, but employer also needs to bear the cost of recovery and its effect to its reputation. This study was carried out to determine the relationship of safety capital (management safety commitment, safety training, extrinsic reward, intrinsic reward, employee involvement, safety communication and safety advice) and safety participation in OSHMS using the resource-based view (RBV) and knowledge-based view (KBV) theories. A total of 100 responses were collected from Malaysian manufacturing firms certified with OSHA18001. Data were analysed using the Smart Partial Least Square (SmartPLS). Results showed that safety training, extrinsic reward and employee involvement directly affect safety participation in OSHMS but not Management Safety Commitment, Intrinsic Reward and Safety Communication. However, Management Safety Commitment and Safety Communication indirectly affect safety participation in OSHMS moderated by high safety advice. As a managerial implication, this research showed that the role played by the safety officers represented by the safety advice is important in enhancing the safety practices and commitment in place to result in a successful safety participation in OSHMS.Â